«Si está parida la gata»: El impacto de partos animales en el imaginario colectivo del Siglo de Oro - Aichinger, Wolfram (Avisos de Viena, 2022)
This article delves into the intersection of human and animal births during the Spanish Golden Age, revealing a society deeply entwined with the processes of procreation. Through historical chronicles, it uncovers a landscape where childbirth, both human and animal, permeated every aspect of daily life. From tales of pregnancies, births, and infanticides to the protection of pregnant animals, the narrative sheds light on the shared experiences and moral perceptions surrounding reproduction. The text explores how animals were not only companions but also integral to understanding human fertility and mortality. Drawing from literary works and legal records, it illuminates the cultural and philosophical implications of this symbiotic relationship, offering valuable insights into the attitudes towards life and death in early modern Spain.